Takfīr in Islamic thought - Timani, Hussam S. (Lexington Books, 2018)
This book provides a comprehensive overview of the concept of takfīr in Islamic thought. It discusses the concept in the doctrines of the major theological schools and in the thought of prominent medieval Muslim theologians.